Reproduction and fecundity of the Irish pollan (Coregonus autumnalis Pallas, 1776), a threatened lake coregonid - Harrod, Chris; Griffiths, D. (2004)
The sex ratio, age at maturation, fecundity, and seasonal development of gonads of pollan (Coregonus autumnalis) in Lough Neagh are described from samples collected between November 1997 and December 1999. Pollan reproductive ecology in the 1990s was similar to that found in the 1970s. Pollan egg size and fecundity differed between years but there were no long-term trends in fecundity despite considerable subsequent eutrophication of the lough and changes in the fish community.